Fostering intergenerational communication through games: an exploratory study on metaphorical life games in family settings - Sun, Ming-xi; Zhao, Zhi-feng; Liu, Huan (Frontiers in Public Health, 2025)
IntroductionExisting research indicates that life review is a crucial means of enhancing intergenerational communication. However, how to effectively facilitate this process through gamification in family settings remains unclear. This study explores how metaphorical life games can promote communication between older adults and adolescents during life review activities, highlighting the relationship between dialogue themes and game design elements that encourage meaningful interaction.MethodsWe played a commercial game by recruiting 24 pairs of family members to play together. Younger partners asked older participants about their relevant memories during the game. The experimental data were analyzed inductively based on thematic analysis.Results and discussionThis study identified the effectiveness of life review through metaphorical games in facilitating communication in intergenerational family relationships by three core mechanisms: communication climate creation, symmetrical intergenerational interaction, and metaphorical expression elaboration. Intergenerational family engagement in metaphorical life games can effectively improve mutual communion and provide game design inspiration for digital games that support intergenerational life review. These findings offer new insights into life metaphor game design strategies and the mechanisms that enhance intergenerational communication.